Propriety of the emergence of the new woman in Kate Chopin's selected fiction - Khoshnood, Ali (2012)
This dissertation tries to depict Kate Chopin’s protagonists’ quests for autonomy, selfdetermination and freedom aligned with nineteenth century female traditions of New Woman’s writing. Chopin deploys some features of the modernist form to refute the Victorian era’s rigid system of normative ethics and this study attempts to show Chopin’s modernist disillusionment with Victorian society’s convention through her depiction of the emergence of modern New Women in her selected fiction. Feminist and psychoanalytical critical approaches are employed to interpret the modern features of the selected texts. The first critical chapter, At Fault, “Lilacs” and “Two Portraits”, unravels how Catholicism and patriarchal hegemonic ideology of the fin-de-siècle served as the primary sources of women’s oppression and their limitation. This chapter also introduces Chopin’s early works as a prologue to her more anthologized works and to show her subtextual intention to depict characters who can emerge, in later works, as more developed, liberated and rebellious females with modern attitudes. This dissertation traces the ways in which the protagonists possess or anticipate the New Woman’s attributions. The Awakening, “A Point at Issue”, “The Story of an Hour” and “A Pair of Silk Stockings” are put in the second critical chapter to examine how the female protagonists adopt the New Woman’s visions to disregard the propriety code of society. The heroines strive to denounce the gospel of motherly self-sacrifice and dismantle the female domestic confinements within patriarchal social orders. All these quests for individuality, self-fulfillment and freedom which were practiced or envisioned by the heroines anticipate the New Woman’s traits and creeds which are examples of a modernist writer’s obsessions. The Awakening’s heroine personality development and her individuation process have not been deservedly examined on psychoanalytic grounds combined with feminist perspective. Thus, the last critical chapter looks at Edna Pontellier’s revolt from the eyes of Jung’s, Briggs Myers’ and Erikson’s psychological theories of human life transition to identify the phases through which Edna Pontellier passes on her journey towards self-discovery. This dissertation tries to delineate that some of the psychological and cultural processes she experiences in her transformation into a new identity are akin to New Woman’s feeling and ideals.